Magnetic susceptibly measurements from the Col de Pré Guittard section (Aptian-Albian, Vocontian Basin, France) - Fatima-Zahra Ait-Itto; Mathieu Martinez; Jean-François Deconinck; Stéphane Bodin (PANGAEA, 2023)
The magnetic susceptibly (MS) measurements were conducted with Agico KLY-3 at the University of Rennes, a total of 3249 samples were measured. The massic MS is reported in m^3/kg To precisely locate the black levels in the CPG-2, a second subsample was performed, 290 samples were selected to be analyzed on carbonate content CaCO3, Total Organic Carbon (TOC), and carbon isotope on organic matter (δ^1^3Corg).